QRS prolongation after cardiac resynchronization therapy is a predictor of persistent mechanical dyssynchrony - Karaca, Oğuz; Omaygenç, Onur; Çakal, Beytullah; Çakal Deniz, Sinem; Barutçu, İrfan; Boztosun, Bilal; Kılıçaslan, Fethi (Springer, 2016)
Purpose Prolonged QRS duration is the main selection criterion for cardiac resynchronization therapy (CRT) which ameliorates left ventricular mechanical dyssynchrony (MD). However, consequences of post-CRT QRS prolongation and residual MD have been poorly evaluated. We aimed to define the predictors of persistent MD and hypothesized that CRT-induced QRS change (Delta QRS) might have an impact on residual MD after CRT. Methods A total of 80 patients receiving CRT were included in the study. Delta QRS was calculated as the difference between the baseline and paced QRS intervals. Residual MD was assessed early after device implantation with a longitudinal dyssynchrony index (Yu index). Significant MD was defined as a Yu index >= 33 msec. Two groups were created based on residual MD and compared according to clinical, electrocardiographic and echocardiographic features. Results Patients with persistent MD had longer paced QRS durations (182.5 +/- 16.2 vs. 165.4 +/- 22.5 msec, p= 0.03) and were less likely to have left ventricular (LV) leads located in the posterolateral vein (53 % vs. 85 %, p= 0.002). The linear correlation between the Delta QRS and the Yu index values was modest (Spearman's rho=-0.341, p= 0.002); additionally, a prolonged QRS was strongly associated with MD after CRT (p= 0.00008). Both LV lead localization and CRT-induced QRS prolongation emerged as the significant predictors of persistent MD. A biventricularly paced QRS more than 10 msec longer than the pre-paced QRS width was predictive of persistent MD after CRT (sensitivity= 80 %, specificity= 62 %). Conclusions Delta QRS was found to be associated with residual MDafter CRT. Ten milliseconds of QRS prolongation predicted persistent MD after CRT.
WOS: 000384843600005
PubMed ID: 26621183
Keywords: Cardiac Resynchronization Therapy; Paced QRS; QRS Prolongation; Mechanical Dyssynchrony